Mediações e distinções entre associativismo e sindicalismo de professores públicos no Ceará (1962- 1992) : A APEOC/Sindicato e o SINDIUTE - Almeida, Danusa Mendes (2015)
This study discusses the mediations and distinctions between association and teacher union, from the unionism phase to the formation of the teacher unions APEOC and SINDIUTE, in Ceará. In the early phase of unionism in the late 1970s, besides the appearance of union leaders, there was the presence of associative model in public school teachers’ movement in Ceará, in APEOC, an organization founded in the 1960s, a period that demarcated the effervescence of associations in secondary school teaching. By the end of the 1980s, with the decline of that model, in the midst of the conformation of the teacher union, two union tendencies set up, which soon after would dispute the leadership in the movement. After the 1988 Carta Magna, with the concession of the right the employees in the civil service have to self-organization, two unions were founded aiming to represent the same category: teachers and civil servants from state and municipal schools in Ceará, and they would have a political and legal dispute for space in the union movement. APEOC/Union, a substitute of the Association, defended the tendency on a propositional unionism. SINDIUTE, in turn, was founded under the speech which proclaimed the defense of a militant unionism. In the face of their singularities, in relation to the national scenario, this research’s main aim is to examine the mediations and distinctions between association and unionism, in the process of foundation of APEOC and SINDIUTE teacher unions. Until then, the association’s role, in the unionism phase, constituted a branch rarely addressed to the literature of the area. Besides, there were a few studies about the associative phase in Ceará. Thus, this study has the following specific aims: to analyze the quantitative aspects of the academic production about association and teacher unionism, as well as the approaches present in the area; to investigate traces of the teacher associative stage and the context of expansion of secondary education in Ceará, and also the educational reforms in the 1970s; to reflect on the formation of the union trends from the unionism to the foundation phase of APEOC and SINDIUTE teacher unions. The field research was one of the supports documentary research, since this allowed a rapprochement with the research object, through sources collected over the period investigated. Our analysis focused on the period between 1962 and 1992. The first one is justified by the fact that it represents the moment of emergence of secondary teachers’ associative movement, during the phase of expansion of secondary education, period when APEOC was founded, the year 1992, on the other hand, marks the foundation of SINDIUTE. During the data collection we interviewed 10 teachers who participated in the movement’s leadership, and 4 teachers who worked in secondary school in the 1960s. The survey also included data collection from public libraries located in the city of Fortaleza. The data analysis showed the importance of educational reforms, including the Reform of 1st and 2nd grades, and leftist movements, during the teacher association’s stage in Ceará. Despite the decline of associative model in teaching movement in the 1980s, its legacy influenced the unionism phase, not only in the configuration of union trends, but also in consolidating APEOC/Union, as one of the major organizations in the state of Ceará.